(untitled) (Revista Gestão & Conexões, 2019)
Empowerment of civil society, beyond its own value, seems to be a nice lever for the efficiency of sustainable development programs and the Brazilian government has embarked on this path. If economic results are quite easy to measure, this is not the case for the evolution of power relationships toward a better balance between social actors’ positions. This article shows how to apply the SocLab framework, a modeling approach that considers power relationships within systems of organized action, to shed light on this issue in The Southern Rural Territory of Sergipe. The simulation results of the model showed significant changes from 2010 to 2016 mainly in the capability, but also in the power of the Associations despite their internal problems to put into practice their ability of negotiation or even of real engagement in the territory.